An isomorphic three‐dimensional cortical model of the pig rostrum. Issue 8 (3rd December 2020) - Ritter, Cindy; Maier, Eduard; Schneeweiß, Undine; Wölk, Tanja; Simonnet, Jean; Malkawi, Safaa; Eigen, Lennart; Tunckol, Elcin; Purkart, Leopold; Brecht, Michael
Abstract: Physiological studies of the last century mapped a somatosensory cortical gyrus representing the pig's rostrum. Here, we describe the extraordinary correspondence of this gyrus to the rostrum. The pig rostrum is packed with microvibrissae ( 470 per hemi‐rostrum) and innervated by a prominent infraorbital nerve, containing about 80, 000 axons. The pig's rostrum has three major skin‐folds. The nostrils have a rectangular medial wall and a funnel‐like lateral opening, nasal channels run obliquely from lateral (surface) to medial (inside). The rostrum gyrus mimics rostrum geometry in great detail. The putative representation of skin folds coincides with blood sinus and folds of the rostrum gyrus. The putative nostril representation is an oblique sulcus running from lateral (surface) to medial (inside). As observed in rodents, Layer 4 is thin in the nostril sulcus. The side of the nostril sulcus representing the medial wall of the nostril is rectangular, whereas the side of the nostril sulcus representing the lateral wall is funnel‐like. Proportions and geometry of the rostrum and the rostrum gyrus are similar, albeit with a collapsed nostril and a larger interindividual variability in the gyrus. The pig's cortical rostrum gyrus receives dense thalamic innervation, has a thin Layer 1 and contains roughly 8 million neurons. With all that, the rostrum gyrus looks like a model of the pig rostrum at a scale of 1:2. Our findings are reminiscent of the raccoon cortex with its forepaw‐like somatosensory forepaw‐representation. Representing highly relevant afferents in three‐dimensional body‐part‐models might facilitate isomorphic cortical computations in large‐brained tactile specialists. Abstract : Body–brain isomorphism of pig rostrum and cortical rostrum gyrus.